FAKTOR-FAKTOR YANG MEMENGARUHI PENDAPATAN ASLI DAERAH KOTA JAKARTA UTARA - Sulistia Anggraeni; Meiriska Febrianti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of the study was to obtain empirical evidence of the effect of hotel taxes, restaurant taxes, entertainment taxes, parking taxes, groundwater taxes, land and building rights acquisition fees on local revenue. The sample of this study was 96 samples, consisting of January to December the period from 2013 to 2020. The data analysis method used to test the hypothesis in this study was purposive sampling. The results of this research data were analyzed using multiple linear regression. The results of the research that have been carried out show that entertainment tax, parking taxes, land and building rights acquisition fees have an influence on local revenue. Meanwhile, hotel taxes, restaurant taxes, and groundwater tax have no effect local revenue.